The Effects of Social Media Tools’ Utilisation on The Provision of Library Resources and Services at The Federal University, Dutsin-Ma, Katsina State, Nigeria - Kakaki Hassan Amadu; Abdulwahab Olanrewaju Issa; Kabir Alabi Sulaiman; Titilola Aminat Bayero Abdussalam (Department Library of Governance Institut of Home Affairs, 2025)
Problem Statement: Social media tools (SMTs) are regarded as valuable platforms for introducing library services through web technologies, benefitting both Library and Information Science (LIS) professionals and library users. The primary aim of utilising SMTs is to promote library services and resources and enhance the relevance of libraries. Purpose: This study examines the effects of SMT utilisation on the provision of library resources and services at the Federal University, Dutsin-Ma, Katsina State, Nigeria. Method: A descriptive survey research design was adopted, targeting a population of 13,410 undergraduate students at the Federal University, Dutsin-Ma. Due to the distribution of respondents across various faculties and departments, a multi-stage sampling technique was employed, incorporating simple random and proportionate sampling methods to select participants. The study use Research Advisor Table (2006) at 95.0% confidence level and degree of accuracy/margin of error, the sample size for this study is 370 from a population of 13,415. Questionnaire was use as instrument for data collection in this study. Descriptive statistics of table and simple percentage with SPSS were used as method of data analysis. Result: The study found out that Twitter, Facebook, Google Plus, YouTube, WhatsApp and Instagram are social media tools for the utilisation of library resources and services provided. The study also found out that e-resources, online and offline databases, subscribed databases, open access, e-books, e-journals, e-learning platform and university repository, as the resources provided to students by the library. Conclusion: The study concludes that social media tools utilisation has effects on provision of library resources and services at Federal university, Dustin-ma. The study recommends that there is the need for the Library to incorporate other SMTs like Facebook, YouTube, Telegram, WhatsApp, Blog, Instagram, LinkedIn, Google Plus, Snapchat and Skype in provision of library resources and services in order to ensure a more effective provision of the resources and services.